Perkembangan Motorik Halus Anak Pada Sentra Seni Dan Kreativitas Di Taman Kanak Kanak Islam Raudhatul Jannah Kota Payakumbuh - Laila Hidayati; Yulsyofriend Yulsyofriend (Jurnal Family Education, 2022)
This study aims to describe the planning, implementation, and evaluation of children's fine motor development at the arts and creativity center at Raudhatul Jannah Islamic Kindergarten, Payakumbuh City. In this study using a qualitative method with a descriptive approach. This study uses data collection techniques in the form of observation, interviews, and documentation. The data analysis technique is carried out by collecting data, reducing data, presenting data and drawing conclusions. Based on the results of the research that has been done, it is stated that the learning planning for children's fine motor development is carried out in accordance with the RPPH. The implementation of learning planning for children's fine motor development consists of setting the playing environment, materials and activities, methods, media and core activities. And also evaluation is carried out by the teacher to see aspects of child development that the child has achieved